Effects Of Age On Emphasis Production In Jordanian Arabic - Ibrahim Eshlash Odeh Almomany (The Journal of Studies in Language, Culture and Society, 2024)
This paper investigates the effect(s) age has on two emphatic sounds, (vis. [sˤ] and [tˤ]) in a sub-dialect of Jordanian Arabic, namely Ajlouni-Jordanian Arabic. This study was for the most part motivated by the neglect of age in studies investigating the socio-phonetics of emphasis in Jordanian Arabic in general and in Ajlouni Jordanian Arabic specifically. The effect of this extra linguistic variable was examined in mono- and bi-syllabic words with the target sounds occurring at both edges of the word. Six vowel qualities were incorporated in the stimuli of this study: the long low-back vowel [a:], the short low-back vowel [a], the long high-front vowel [i:], the short mid-high front vowel [ɪ], the long high-back vowel [u:] and the short mid-high back vowel [ʊ]. The data were collected from twelve native speakers of the dialect, with each yielding 96 tokens. As for the acoustic means that were conducted on the gathered data, the following were used: consonant duration (CD), Voice Onset Time (VOT), F1, F2 and F3. The figures obtained in this study confirm that only VOT is significant as far as age is concerned.